2022
DOI: 10.4178/epih.e2022005
|View full text |Cite
|
Sign up to set email alerts
|

Association of participation in the Northern Finland Birth Cohort 1986 with mental disorders and suicidal behaviour

Abstract: Objectives: In the prospective follow-up studies participants are normally contacted during the follow-up. Even though the idea is not to intervene, the studies conducted during follow-up may affect the target population. Our hypotheses were that the participation to prospective Northern Finland Birth Cohort 1986 study (NFBC 1986) increases the use of mental health services and reduces the suicidal behaviour due to participation in follow-up study. due to intervention effect. Methods:The study cohort NFBC 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The participation bias in epidemiological follow-up studies has previously been under-examined, and the results need to be replicated. In a previous study, an association between the use of mental health care services and participation in the NFBC1986 study was found [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participation bias in epidemiological follow-up studies has previously been under-examined, and the results need to be replicated. In a previous study, an association between the use of mental health care services and participation in the NFBC1986 study was found [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study did find an association between the Northern Finland Birth Cohort 1986 (NFBC1986) and mental disorders; the female members of the NFBC1986 had less psychiatric diagnoses at age 2 to 28 years than the comparison cohort [39]. Both of the NFBC studies are prospective longitudinal birth cohorts with multiple follow-ups.…”
Section: Plos Onementioning
confidence: 99%